Vascular homeostasis in atherosclerosis: A holistic overview - Xu, Suowen; Lyu, Qing Rex; Ilyas, Iqra; Tian, Xiao-Yu; Weng, Jianping (Frontiers in Immunology, 2022)
Atherosclerosis refers to the deposition of lipids and the co-existence of inflammation and impaired inflammation resolution in pan-vasculature, which causes lumen narrowing, hardening, plaque formation, and the manifestation of acute cardiovascular events. Emerging evidence has suggested that vascular circulation can be viewed as a complex homeostatic system analogous to a mini-ecosystem which consists of the vascular microenvironment (niche) and the crosstalk among phenotypically and functionally diverse vascular cell types. Here, we elucidate how cell components in the vascular wall affect vascular homeostasis, structure, function, and atherosclerosis in a holistic perspective. Finally, we discuss the potential role of vascular-stabilizing strategies including pharmacotherapies, natural substances and lifestyle modifications, in preventing cardiovascular diseases by preserving vascular integrity and homeostasis.